STUDI PERUBAHAN PROTEIN TERLARUT SELAMA PERKECAMBAHAN BIJI WIJEN (Sesamun indicum L.) MENGGUNAKAN PENDEKATAN RESPON SURFACE METHODOLOGY - Suhendra, Lutfi (Agrotekno; Vol. 11, No. 2 Januari 2005, 2012)
The research objective was to study the soluble protein change during process seedgermination. Seed sprout were made in dark room at the room temperature (30 0C) withseveral combination treatment of 3 factor in 5 levels for each factor. The factors are (i)duration of germination process; (ii) duration of soaking process; and (iii) pH of soakingsolution. The analysis of soluble protein was undertaken from extracted sprouts. Data wasanalysed by using the Respon Surface Methodology (RSM) with the central compositedesign (CCD). The research results indicated that the minimum of soluble protein (theincubation of 24 hour in temperature 50 0C with minimum value 4,54% wet weight) wasobtained from the process of 36 hours of germination process, 100 minute of soakingprocess and in pH of 5,65.
Keywords: Protein terlarut, kecambah biji wijen, response surface methodology